A literature review: The Effectiveness Psychoeducation Therapy To Treatment Psychological Disorder In Patients Chronic Diseases - Novita Ayu Indriani; Ambar Relawati (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: The treatment process of chronic diseases that lasts a long time can cause psychological problems because of the boredom they cause. Psychological disorders can cause patients won’t continue treatment, so that an intervention is needed to treatment the disorder. Psychoeducation therapy is a relevant therapy for dealing with psychological disorders because it directly affects the patient’s psychology. Objective: To review the journals that explain the effectiveness of psychoeducation interventions to treatment psychological disorders in patients with chronic diseases.Methods: The database used in this review are studies published in PubMed, EBSCOhost, Scopus, and Google Scholar. Critical appraisal in research that appropriate the inclusion criteria will be conducted dependently by the author and adviser using the JBI Critical Appraisal Checklist for Quantitative Research.Results: A total of ten articles were reviewed. The majority of the ten articles reviewed proved that psychoeducation therapy was effective in treatment psychological disorders with p<0,05, but there was 1 variable from the articles that was not proven effective with p>0,05.Conclusion: Psychoeducation therapy is effective in treating psychological disorders in patients with chronic diseases although with different duration and non-uniform follow-up.